2017
DOI: 10.1016/j.molliq.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and correlation of phase equilibria in aqueous two-phase systems containing functionalized magnetic ionic liquids and K2HPO4/K2CO3/Na2CO3 at 298.15 K

Abstract: Functionalized magnetic ionic liquids (MILs)([C 2 TMG][TEMPO-OSO 3 ], [C 3 TMG][TEMPO-OSO 3 ], [C 4 TMG][TEMPO-OSO 3 ]) and three inorganic salts (K 2 HPO 4 /K 2 CO 3 /Na 2 CO 3) were used to form aqueous two-phase system at 298.15 K. Three classical experienced equations were applied for the correlations of the binodal curves. All of them demonstrated satisfactory performance in data association. The binodal curves were investigated in detail. Both K 2 HPO 4 and K 2 CO 3 was excellent phase forming salts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Ionic liquids (ILs), a class of non-molecular solvents at room temperature, 18 which generally consist of an organic cation and a weak nucleophilic anion, have drawn widespread attention of researchers due to their superior properties such as negligible volatility, thermal and chemical stability, wide liquid range, non-flammability, and good solubility. 19 They often replace hazardous organic solvents and serve as an environmental friendly, non-volatile and recyclable reaction medium. Furthermore, they are much safer in the high-temperature or high-pressure synthetic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs), a class of non-molecular solvents at room temperature, 18 which generally consist of an organic cation and a weak nucleophilic anion, have drawn widespread attention of researchers due to their superior properties such as negligible volatility, thermal and chemical stability, wide liquid range, non-flammability, and good solubility. 19 They often replace hazardous organic solvents and serve as an environmental friendly, non-volatile and recyclable reaction medium. Furthermore, they are much safer in the high-temperature or high-pressure synthetic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid extraction is used in chemical technology to extract and separate a wide range of organic and inorganic compounds. Creation of extraction systems without organic solvent is a promising direction in the development of extraction methods, one of which is the aqueous two-phase systems (ATPS). These systems have exceptional advantages over classical extractants, such as environmental safety, fire safety, and accessibility. Aqueous two-phase systems can be used in biotechnological processes, pharmaceuticals, for the extraction of metal ions, and so on, which is confirmed by a large number of articles and reviews.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple reaction steps involving laborious and time-consuming procedures based on filtration, drying, and purification were required for synthesizing the [N 1 1 n 2OH ]Br and [N 1 1 n 2OH ]Cl ionic liquids, Na[TEMPO-OSO 3 ], and the MILs. Other studies involving the synthesis of organic MILs have been recently reported[55,59,60].…”
mentioning
confidence: 99%